2007
DOI: 10.12702/1984-7033.v07n04a04
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis of upland cotton cultivars

Abstract: Crosses involving eight commercial upland cotton cultivars were performed in all possible combinations to generate 28 hybrids. The eight parental genotypes were also evaluated. A field experiment was conducted using a triple Latice design (6 x 6) in Itumbiara, Brazil, during the 2000/01 growing season. Data of the following agronomic and fiber traits were collected: seedcotton yield, lint yield, seed index, picked lint percent, index of production and earliness, micronaire index, fiber strength, fiber length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 3 publications
5
21
0
Order By: Relevance
“…Parents with dominant genes were responsible for increased lint % in both generations. The present results are also in line with the findings of Tang et al (1993), McCarty et al (1996McCarty et al ( , 2004a, Hussain et al (1999), Ahmad et al (2003b), Yuan et al (2005), Aguiar et al (2007) and Ali and Awan (2009), who reported additive type of gene action with partial dominance for inheritance of lint%. However, Tang et al (1996), Godoy and Palomo (1999), Basal and Turgut (2005), Iqbal et al (2005), Mei et al (2006), Esmail (2007 and Gamal et al (2009) concluded non-additive type of gene action with over-dominance for lint %.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Parents with dominant genes were responsible for increased lint % in both generations. The present results are also in line with the findings of Tang et al (1993), McCarty et al (1996McCarty et al ( , 2004a, Hussain et al (1999), Ahmad et al (2003b), Yuan et al (2005), Aguiar et al (2007) and Ali and Awan (2009), who reported additive type of gene action with partial dominance for inheritance of lint%. However, Tang et al (1996), Godoy and Palomo (1999), Basal and Turgut (2005), Iqbal et al (2005), Mei et al (2006), Esmail (2007 and Gamal et al (2009) concluded non-additive type of gene action with over-dominance for lint %.…”
Section: Discussionsupporting
confidence: 92%
“…Tang et al (1996), Basal and Turgut (2005), Iqbal et al (2005), Khan et al (2005), Esmail (2007 and Aguado et al (2008) also mentioned that dominant gene effects were higher than additive for yield, because additive variance was found smaller than dominant components and that expression was also confirmed by degree of dominance. However, Luckett et al (1989), Ahmad et al (2003a,b), Aguiar et al (2007) and Gamal et al (2009) mentioned that for seed cotton yield, the additive gene effects were more important under favorable conditions but under stress, the nonadditive effects of the genes were more imperative. But heritability (h 2 ) values were much smaller relative to broad sense heritability in both environments indicating that the additive component was smaller than the other components of variance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quadratic components shown in Table 1 (2007) and Hinze et al (2011). For SFI, similar results were obtained by Aguiar et al (2007) and Zeng et al (2011). Regarding SPI, results are supported by Aguiar et al (2007), which observed the predominance of additive effects in the control of fiber spinning in upland cotton genotypes.…”
Section: Combining Abilitiessupporting
confidence: 68%
“…'BRS 293' was originated from crosses between Stoneville 132 (a widely cultivated cotton cultivar with pedigree DES 56 x TAMCOT SP37) and Delta Opal (a high-yielding cotton cultivar with pedigree DP 5816 x Sicala 33), carried out in 2000 at Randonópolis, MT. Hybrid combinations with cultivar Delta Opal are recommended for the improvement of seedcotton yield, lint yield, seed index, index of production, and earliness (Aguiar et al, 2007 40.5 to 42.5%; micronaire reading ranged from 3.9 to 4.5; fiber length (SL 2.5%) from 28.5 to 30.5 mm; relative strength from 28.3 to 32.9 gf tex -1 ; reflectance from 72 and 82%; yellowness (+b) from 6.5 to 10.0; short fiber index from 3.9 to 6.3; spinning consistency index from 140 to 160; the fiber spin character could be defined as very good (Table.2).…”
Section: Genetic Origin and Developmentmentioning
confidence: 99%